Construction of a cellulase hyper-expression system in Trichoderma reesei by promoter and enzyme engineering - Zou, Gen; Shi, Shaohua; Jiang, Yanping; van den Brink, Joost; de Vries, Ronald P; Chen, Ling; Zhang, Jun; Ma, Liang; Wang, Chengshu; Zhou, Zhihua (Microbial cell factories, 2012)
Trichoderma reesei is the preferred organism for producing industrial cellulases. However, a more efficient heterologous expression system for enzymes from different organism is needed to further improve its cellulase mixture. The strong cbh1 promoter of T. reesei is frequently used in heterologous expression, however, the carbon catabolite repressor CREI may reduce its strength by binding to the cbh1 promoter at several binding sites. Another crucial point to enhance the production of heterologous enzymes is the stability of recombinant mRNA and the prevention of protein degradation within the endoplasmic reticulum, especially for the bacteria originated enzymes.In this study, the CREI binding sites within the cbh1 promoter were replaced with the binding sites of transcription activator ACEII and the HAP2/3/5 complex to improve the promoter efficiency. To further improve heterologous expression efficiency of bacterial genes within T. reesei, a flexible polyglycine linker and a rigid α-helix linker were tested in the construction of fusion genes between cbh1 from T. reesei and e1, encoding an endoglucanase from Acidothermus cellulolyticus. The modified promoter resulted in an increased expression level of the green fluorescent protein reporter by 5.5-fold in inducing culture medium and 7.4-fold in repressing culture medium. The fusion genes of cbh1 and e1 were successfully expressed in T. reesei under the control of promoter pcbh1m2. The higher enzyme activities and thermostability of the fusion protein with rigid linker indicated that the rigid linker might be more suitable for the heterologous expression system in T. reesei. Compared to the parent strain RC30-8, the FPase and CMCase activities of the secreted enzyme mixture from the corresponding transformant R1 with the rigid linker increased by 39% and 30% at 60°C, respectively, and the reduced sugar concentration in the hydrolysate of pretreated corn stover (PCS) was dramatically increased by 40% at 55°C and 169% at 60°C when its enzyme mixture was used in the hydrolysis. This study shows that optimizations of the promoter and linker for hybrid genes can dramatically improve the efficiency of heterologous expression of cellulase genes in T. reesei.